The Comparison of Satirical Jokes in the Reels of @Podcastkeselaje and The Daily Show with Trevor Noah - Namiratusshofa Siregar; Rohani Ganie; Rahmadsyah Rangkuti (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Despite the rise of social media platforms such as Instagram, satire remains an effective way to discuss and criticize current issues and states of affairs without offending communities. Hence, this research examines the satirical jokes found in the @podcastkeselaje Instagram account and The Daily Show With Trevor Noah in order to discuss social phenomenon that exist between different states. The objectives of this study are to classify the types of satire, describe the way of the satirical jokes are delivered in the reel video and The Daily Show, and explain the comparison of satirical jokes found between Indonesian and American culture. The data was collected from 15 reel videos of @podcastkeselaje official Instagram account with a total of 67 utterances, compared to 4 episodes of Trevor Noah’s Show with a total of 11 utterances. This qualitative study employs Critical Discourse Analysis (CDA) by Fairclough as the approach and Abrams and Harpham’s concept of satire. Based on the results of the study, Horatian satire (28,2%), Juvenalian satire (20,6%), and Menippean satire (51,2%) are the most frequently found in the reels video. The satirical jokes found in the reel videos were delivered in a direct way, either by serving humor or insulting the target harshly and indirectly expressing the satire to the target. According to the findings, the comparison of Indonesian and American satire is clearly depicted by the similarities in social, political, and racism issues due to similar social backgrounds; if Indonesia consisted of various tribes, America is consisted of various ethnicities. Both of the nations adhere to a democratic system which refers to the implementation of Human Rights no matter what their races, they are totally different in cultural cases related to Eastern and Western norms and values. Therefore, the background of a culture impacts the realization of the satire.